Infraestrutura e inclusão: uma análise do ambiente escolar para alunos com deficiência - Elias, Vitória Régia De Souza (2021)
The school environment is historically marked by traditional teaching practices, which do not envision or contemplate the universe of special education and, above all, inclusion. This study aimed to analyze the levels of inclusion of children with disabilities in the school environment and their relationship with infrastructure, in public and / or private schools. It was a descriptive research, with a quantitative approach and a survey. The research was carried out in two Universities and a Faculty, all located in the East Zone of the city of São Paulo. The participants corresponded to 142 students duly enrolled in undergraduate courses - Graduation in the aforementioned Universities and recent graduates from 2018 to 2019. For data collection, two instruments were used, built by the researcher: one for attracting participants: 1) Screening - Registration form, and the other to understand the school infrastructure, levels of inclusion and its relationship with the population studied: 2) Evaluation Questionnaire on School Infrastructure, its Adjacent Spaces and the Levels of Inclusion of Students with Disabilities. The data collection was carried out individually, using the Google Forms tool, and the access links to the forms were sent via email, WhatsApp group and Telegram to the students participating in the research. After collection, the data were entered (coded and in some cases grouped) in an Excel spreadsheet 2010 version, and later statistically treated with the software R version 4.0.3 (2020-10-10). The results obtained were analyzed using descriptive and inferential statistical techniques and demonstrated that students with disabilities, when they access regular schools and common classes, are unable to reach the inclusion levels in an integral way and that the school infrastructure is not adequate to receive them, resulting in their exclusion.